Bone remodelling in inflammatory arthritis. (19th December 2012) - Goldring, Steven R; Purdue, P Edward; Crotti, Tania N; Shen, Zhenxin; Flannery, Merrilee R; Binder, Nikolaus B; Ross, F Patrick; McHugh, Kevin P
Abstract : The inflammatory arthropathies that include rheumatoid arthritis, the seronegative spondyloarthropathies and systemic lupus erythematosus are characterised by marked alterations in the architecture and structural integrity of peri-articular bone; however, the pattern and natural history of the skeletal changes differs in these conditions. In part, this can be attributed to differences in the primary anatomical site of the inflammation, but also there is evidence that there are differences in the biological properties and products produced by inflammatory tissues. This review will focus on recent advances in the understanding of the cellular and molecular mechanisms that contribute to the differential pattern of articular bone remodelling in these prototypical inflammatory forms of arthritis.